Proceedings of the 5th ACM Workshop on Privacy in Electronic Society 2006
DOI: 10.1145/1179601.1179621
|View full text |Cite
|
Sign up to set email alerts
|

A study on the value of location privacy

Abstract: This paper introduces results of a study into the value of location privacy for individuals using mobile devices. We questioned a sample of over 1200 people from five EU countries, and used tools from experimental psychology and economics to extract from them the value they attach to their location data. We compare this value across national groups, gender and technical awareness, but also the perceived difference between academic use and commercial exploitation. We provide some analysis of the self-selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 2 publications
1
83
1
Order By: Relevance
“…What would happen if people learned that others are making money from their PI? An experiment conducted by Cvrcek, Vashek et al (2006) on location data showed that, when study participants learn that their PI will be used not only for academic but also for commercial purposes, 25-57% of participants increased the amount of money that they wanted to receive for study participation. The desire to participate in the commercial exploitation of one's PI assets may be due to fairness perceptions.…”
Section: H1mentioning
confidence: 99%
“…What would happen if people learned that others are making money from their PI? An experiment conducted by Cvrcek, Vashek et al (2006) on location data showed that, when study participants learn that their PI will be used not only for academic but also for commercial purposes, 25-57% of participants increased the amount of money that they wanted to receive for study participation. The desire to participate in the commercial exploitation of one's PI assets may be due to fairness perceptions.…”
Section: H1mentioning
confidence: 99%
“…A number of recent empirical studies conducted by information privacy scholars have examined that in a variety of contexts (Acquisti, John, & Loewenstein, 2013), from the disclosure of personal information online (Hann, Hui, Lee, & Png, 2007) to location data (Cvrcek, Kumpost, Matyas, & Danezis, 2006) and beyond (for thorough reviews of information privacy research, see Bélanger & Crossler, 2011;Cvrcek et al, 2006;Hong & Thong, 2013;Li, 2012;Pavlou, 2011;and Smith et al, 2011). Yet there is still substantial work to be done.…”
Section: Studying the Perceived Value Of Transparency And Privacymentioning
confidence: 99%
“…Recently, there are debates on persuasive ethics of using information systems among scholars [18]. The discussion emphasizes on abuses and malfunctions of using information systems in several theories of behavior.…”
Section: E Privacy and Ethics In Information Systemsmentioning
confidence: 99%